Uma ferramenta para visualização e simulação de exercícios navais em cenários marítimos reais - Arraes, Kátia Alves (2006)
This work has as objective builds a tool for Visualization and Simulation of Naval Exercises in Real Marine Sceneries. This tool was developed considering as the Brazilian Navy controls and it analyzes their exercises. The Real Marine Scenery is described mainly by the use of an image file in the format BSB (Maptech), format this adopted for reproduction of Nautical Chart and used by several Institutes Hydrographic in the world, as: Argentina, Brazil, Canada, Mexico, United States and other. This format allows the use of images great resolution, that are geographic referred, that specifies the geodesic datum source of the chart, that describes palettes of alternative colors for observation of the chart and it uses a compression form and own decompression of the data. For that, a detailed study of this format type is also described in this work, that concentrates on the aspects of data compression, storage forms, color description and geographical coordinates. The Real Marine Scenery is used as background, where the exercises are visualized through the introduction of the ship profiles based in the symbols adopted by the Brazilian Navy, considering the real geographical coordinates defined by Global System Position (GPS). The positioned points and the lines that describe the routes are vectorial elements that are included in the raster chart. The study also presents an abbreviation revision of the process of evolution of the navigation from the past to the Electronic Chart at present time.